Useful markers for differential diagnosis of oncocytoma, chromophobe renal cell carcinoma and conventional renal cell carcinoma - Geramizadeh Bita; Ravanshad Mahmoud; Rahsaz Marjan (Wolters Kluwer Medknow Publications, 2008)
Renal oncocytoma, conventional RCC (granular cell type) and chromophobe RCC have different prognosis. Sometimes differentiation between them is difficult in HandE slides. In a 5-year study of 128 renal tumors, we selected 76 cases [30 conventional RCC (CRCC), 16 papillary RCC, 21 chromophobe RCC (ChRCC), 8 oncocytoma, 1 collecting duct carcinoma (cdc)] and staining with Hale′s colloidal iron, CK7, CK8, CK18, CK19, CK20, Vimentin, EMA, CD10 and RCC marker were done. No significant difference was seen between renal tumor subtypes with CK8, CK18, CK19, CK20 and EMA. The most useful markers were Vimentin, CK7, CD10, RCC marker and Hale′s colloidal iron. Hale′s colloidal iron staining with diffuse reticular fine cytoplasmic pattern was present in ChRCCs, but was absent in other subtypes and oncocytomas. Vimentin, CK7, CD10, RCC marker and Hale′s colloidal iron can be used for the differential diagnosis of problematic epithelial tumors of kidney (CRCC, ChRCC and oncocytoma) - i.e. ChRCC: Vimentin, CD10 and RCC marker - negative, CK7 - positive and positive diffuse fine reticular cytoplasmic pattern of Hale′s colloidal iron; oncocytoma: Vimentin, CK7, RCC marker and CD10 - negative and Hale′s colloidal iron - negative; CRCC: CK7 - negative, Vimentin, CD10 and RCC marker - positive and Hale′s colloidal iron - negative.